The Practice of Interpretation of As-Sa'di And Muhammad Ali Ash-Shabuni (A Comparative Study of Q.S. Al-Baqarah/2: 284-286): Praktik Penafsiran As-Sa'di Dan Muhammad Ali Ash-Shabuni (Studi Komparatif Terhadap Q.S. Al-Baqarah/2: 284-286) (Takwil: Journal of Quran and Hadith Studies, 2024)
This study contains the specialty of the closing of surah al-Baqarah verses 284-286. The last verse of the closing of al-Baqarah in addition to having a message in its content, it also has its own impression for Muslims. This verse is often read during zhikr, tahlil, and often also read when finished praying. This study uses two books of tafsir, namely tafsir as-Sa'di by as-Sa'di and tafsir Shafwatut Tafasir by Muhammad Ali Ash-Shabuni. Of these two books of interpretation, when viewed from the systematics of interpretation has a difference. As-Sa'di interprets the verses one by one. While ash-Shabuni interprets by grouping these three verses, but there is a cut in verse 285 with 286, but ash- Shabuni does not bring up the theme of the group of verses. In the interpretation of as -Sa'di he interpreted by bringing up the aspect ofbalaghahn only, while in the interpretation ofash-Shabuni, he brought up munasabah, lughah, asbabun nuzul, tafsir, balaghah and faidah in his interpretation. In this case, the author is interested in further discussing these two books of interpretation related to Q.S. Al-Baqarah: 284-286 by looking at the interpretation practices carried out by as-Sa'di and Ali-Ash-Shabuni with the title Interpretation of As-Sa'di and 'Ali Ash-Shabuni. This study uses literature research method on the book Tafsir al-Karim al-Rahman fi Tafsir Kalam al-Manan by as-Sa'di and tafsir Shafwatut Tafasir by Muhammad Ali Ash-Shabuni. As-Sa'di and Ali Ash-Shabuni both explain the aspect of balaghah in their tafsir. In addition, As-Sa'di and Ali Ash-Shabuni also both explain the aspect ofmunasabah verse. When viewed from the difference, tafsir Sa'adi interprets the verse very concisely and short. In contrast to Ali Ash- Shabuni in tafsir Shafwatut Tafasir, the explanation of the meaning is ijmali and tahlili at once. Ali Ash-Shabuni also explains the munasabah of the verse, lughah, asbabun nuzul, tafsir balaghah and its faidah.